A two-dimensional material removal model in magnetorheological finishing. (1st October 2008) - Chen, Feng Jun; Yin, Shao Hui; Ohmori, Hitoshi; Lin, Wei Min
Magnetorheological Finishing (MRF) is a new advanced optics and precision mould manufacturing technology. According to the sharp rheological characteristics of magnetorheological fluid in the magnetic field, and based on earlier research, the Preston equation, the Reynolds equation and its boundary conditions are revised and extended. The material removal model in two-dimensional directions is built and analysed by simulation. Especially the influence of workpiece materials is considered. Finally, the MRF experiment is carried out, and the influence rules of the immersed depth and material kinds are studied. The experimental data are compared with the material removal model result, which confirms the mathematical model validity. The model establishment and the processing experiment will provide the important theory and experimental references for deterministic Computer Numerical Control (CNC) nanometer process of complex optics parts.